Sustained training with novel distractors attenuates the behavioral interference of emotional pictures but does not affect the electrocortical markers of emotional processing - Ferrari, Vera; Canturi, Francesca; De Cesarei, Andrea; Codispoti, Maurizio (Frontiers in Psychology, 2024)
Research has recently shown that behavioral interference prompted by emotional distractors is subject to habituation when the same exemplars are repeated, but promptly recovers in response to novel stimuli. The present study investigated whether prolonged experience with distractors that were all novel was effective in shaping the attentional filter, favoring stable and generalizable inhibition effects. To test this, the impact of emotional distractors was measured before and after a sustained training phase with only novel distractor pictures, and that for a group of participants depicted only a variety of neutral contents, whereas a different group was exposed only to emotional contents. Results showed that emotional interference on reaction times was attenuated after the training phase (compared to the pre-test), but emotional distractors still significantly interfered with task performance. The two groups did not differ in terms of training effect, suggesting that the distractor suppression mechanism developed during training was not sensitive to the affective category of natural scenes with which one had had experience. The affective modulation of neither the LPP or alpha-ERD showed any effect of training. Altogether, these findings suggest that sustained experience with novel distractors may attenuate attention allocation toward task irrelevant emotional stimuli, but the evaluative processes and the engagement of motivational systems are always needed to support the monitoring of the environment for significant cues.